Dampak Sosial Ekonomi dan Lingkungan Fisik Masyarakat Akibat Pengembangan Hotel di Kota Yogyakarta - Murti, Chatarina Candra; Rofi, Abdur (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
Yogyakarta is one city ofÂ destination for tourism in Indonesia. It make impact for improvement of shelter space and hotel. Construction of hotels in Yogyakarta City raise the pro and contra among the society. This research compare between two hotels, Tentrem and Cavinton Hotel. Both of the hotelshave a similar background is a star hotel and equally hotel ever built before the regular classroom. The purposes of this research are, 1) Find out the socio-economic impacts because of the construction of Tentrem and Cavinton Hotel 2) Find out the comparison of socio-economic impacts because of the construction of Tentrem and Cavinton Hotel. Â The method in this research are, quantitative and qualitative. Technique data collection using questionnaires and observation while using sampling line transect so that the sample number is not same in both hotels. Hotel cavinton were 40 responden and Hotel Tentrem 30 responden. The results of this research showed that 1) The effects of construction of Tentrem and Cavinton Hotel are, social, economic, and physical environment impacts.. Physical environment impacts are, land conversion, water condition, and waste. 2) Social and economic impacts is higher of Tentrem Hotel, mean while physical environment impacts is higher of Cavinton Hotel.